Notes on the histories of history in the Soviet Union - Banerji, Arup (2006)
During most of the lifespan of the Soviet Union, history and historiography remained subject to specific restrictive constraints. It was during the last few years pending its demise that an "unleashing of the energy of history" produced a flood of new work in various genres, that fundamentally challenged received wisdom. The foci of this essay are, firstly, to depict the manner by which the Soviet regime controlled research institutions, publications and themes in the domain of history and secondly, to chart the shifting positions concerning discussions of key events in Soviet history. The archives and the textbook hav been singled out as exemplifying Soviet policies. The essay is interpretative and illustrative; it does not lay any claim to serving as an exhaustive chronicle of the histories of history in the USSR. - Reproduced.
Keywords: Soviet union - Politics and government; Politics and government